Effects Of Good Corporate Governance And Corporaate Social Responsibility Towards Firm Value - Yusbardini; Edward Widjaja (Jurnal Ekonomi, 2022)
This research’s purpose is to see if VF is effected by GCG and CSR, this research is made due to the results that the author has read from the previous research, where in some cases resulted GCGhas an effect towards VF and in some other case only CSR has an effect towardsVF. Thus the author decided to create this research in hope to clear the fluctuation of the previous research, the author hopes that this research can help investors that want to invest their funds and also the people reading this article The sample of the research is picked using the purposive sampling method thus leaving 4 Government banks. Based on the Multiple linier regression it can be concluded that GCG has a positive impact on Value of the Firm and CSR also has a positive impact on VF.